Knowledge of Dental Avulsion Among Emergency Physicians: A Survey Study - Seçil Çalışkan; Ebru Delikan; Sena Kızılaslan; Özge Özbek (Galenos Yayinevi, 2021)
Aim:Dentoalveolar injuries are complex conditions affecting teeth and surrounding tissues and are frequently seen in children or adolescents. The purpose of this study was to investigate the levels of knowledge on dental avulsion among emergency physicians (EPs).Materials and Methods:A questionnaire was used to investigate EPs' level of knowledge and therapeutic approaches to avulsion. One hundred EPs were included in the study. The questionnaire was mailed to participants, and the data obtained were evaluated. Descriptive statistics and chi-square tests were used for statistical analysis.Results:Our results showed that although EPs frequently encountered dental traumas, their medical education had not included dental emergencies. The knowledge level of dental avulsion of all EPs included in the study was as follows; 24% low, 56% moderate and only 18% high.Conclusion:EPs possessed inadequate knowledge concerning the immediate treatment of dental avulsion. The treatment of avulsion should be included in the medical curriculum. This will result in appropriate emergency treatments in dental avulsion being provided in emergency settings.